Experimental analysis of flashover characteristics for overhead power lines based on the lightning fractal model - ZHAN Jintao; YANG Tianyi; GUO Jun (电力工程技术)
In recent years, a fractal model that can reflect the tortuosity and dispersion of lightning has been gradually used in the research of lightning shielding performance for overhead power lines, based on electrical geometric models and pioneering development models. In this paper, a 1 ∶40 scaled experimental platform based on the equivalence between simulation experiments and natural lightning is constructed, with the ZB6T type tower commonly used in 500 kV transmission lines as the research object. A negative polarity impulse wave of 160/2 500 μs is applied to investigate the relationship between flashover probability, spatial distribution, and protection angle. Based on the WZ model and finite difference method, a lightning fractal model is established, and the characteristics of line flashover are simulated and analyzed under the configuration of the scaled experimental gap. Both the simulation experiments and the simulation results indicate that the points with high flashover probability are concentrated near the transmission line, and the overall flashover space presents a parabolic shape, conforming to the flashover law. As the protection angle decreases, the flashover probability decreases correspondingly, and the flashover space slightly decreases. The simulation results verify the reliability of the simulation experiments and the correctness of the model. Comparing the simulation results with the experimental data, the model shows a high level of reliability.